Analisis Komparatif Implementasi Kredit Usaha Rakyat Perspektif Hukum Ekonomi Syariah Pada Pegadaian Syariah dan Bank Syariah Indonesia - Safaruddin, Safaruddin (Jurnal Keuangan dan Perbankan Syariah, 2024)
This research aims to provide a comprehensive overview of the similarities and differences in the application of KUR in the context of sharia economic law in the two financial institutions and make a meaningful contribution to the development of sharia financial practices in Indonesia. This research uses a descriptive qualitative approach with a comparative study method to understand and compare the implementation of Kredit Usaha Rakyat at Pegadaian Syariah and Bank BSI based on the principles of sharia economic law. Pegadaian Syariah distributes KUR through four stages with a Rahn Tasjily contract, while Bank Syariah Indonesia (BSI) follows six stages with a Murabahah Bil Wakalah contract. Pegadaian Syariah focuses on productive sharia businesses of at least 6 months, offering installments of 6-24 months, and verification of 3-4 weeks, while BSI prioritizes the service, production, and agriculture sectors, with maximum installments of 36-48 months, and requires collateral for ceilings above IDR 100,000,000. This research uses a sharia economic law approach to analyze the implementation of KUR in Pegadaian Syariah and Bank BSI, highlighting compliance with Islamic law. Through a comparative study between the two institutions, this research provides specific insights into variations in the implementation of KUR in a sharia context that have not been widely discussed in the literature.